Experimental and numerical investigations on dynamic tensile behavior of a ZrB2-SiC ceramic - He, R.; Cao, J.; Yang, K.; Wang, L.; Kong, D. (Archives of Mechanics, 2023)
The dynamic tensile behavior of a ZrB2-SiC ceramic was investigated via split Hopkinson pressure bar tests and a bond-based peridynamic model. The experimental results showed that the peak dynamic splitting tensile stress increased linearly with the strain rate. The dynamic tensile stress history and fracture pattern exhibited a significant strain-rate dependence. In simulation, the strain-rate dependent on the critical energy release rate was introduced to predict the dynamic tensile behavior of the ZrB2-SiC ceramic. The numerical results were in good agreement with the experimental results, verifying the applicability of the peridynamic model. The maximum error of the peak dynamic splitting tensile stress between the experimental and numerical results was no greater than 6%. Moreover, the effect of the strain rate on the fracture patterns of the ZrB2-SiC ceramic composite can be well predicted by the peridynamics method. The ZrB2-SiC composite specimen split into two large fragments with additional small fragments under dynamic splitting tension. With the increase of strain rate, the main crack propagation and branching led to a larger fracture region in the middle of the specimen.